Intersectionality in Modern English Young Adult Literature: Gender, Race, and Neurodiversity - Ika Wulandari (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Intersectionality studies in contemporary English-language young adult literature are becoming increasingly relevant in revealing the complexity of character identities and their experiences. This article examines the representation of gender, race, and neurodiversity in Young Adult (YA) literature as part of narratives that reflect and challenge social norms. Using a qualitative approach based on discourse analysis and intersectionality theory, this study explores how YA authors bring together multiple identity categories to create authentic and inclusive narratives. Findings suggest that modern YA works not only feature character diversity, but also demonstrate the interaction between complex and interrelated dimensions of identity.